Assessing the specific psychopathology of binge eating disorder patients: interview or self-report? - Wilfley, D; Schwartz, M; Spurrell, E; Fairburn, C (1997)
Research addressing the assessment of binge eating and associated eating disorder psychopathology has steadily increased in recent years. Few studies have examined the relationship between the various assessment methods. This study compared an investigator-based interview, the Eating Disorder Examination (EDE), with a self-report version of that interview, the EDE-Q. Fifty-two individuals (six men and 46 women) with binge eating disorder (BED) completed both instruments. Modest-to-good agreement and significant correlations (P < 0.0001) were found between the two methods on all four subscales assessing specific eating disorder psychopathology (i.e., Restraint, Eating Concern, Weight Concern, and Shape Concern subscales). However, higher levels of disturbance were consistently reported on the EDE-Q than the EDE interview. The two methods were not significantly or reliably related to one another when assessing binge eating. This may be due in part to the difficulty inherent in identifying binges in subjects with BED. Examination of individual item scores suggest that it might be possible to improve the performance of the EDE-Q by clarifying the definitions of certain complex features, although this should not be at the expense of compromising the practical utility of its self-report format.